The Impact of the Global Financial Crisis on Off-Farm Employment and Earnings in Rural China - Huang, Jikun (2012)
This paper examines the effect of the financial crisis on off-farm employment of China's rural labor force. Using a national representative dataset, we find that there was a large impact. By April 2009 off-farm employment reached 6.8% of the rural labor force. Monthly earnings also declined. However, while we estimate that 49 million were laid-off between October 2008 and April 2009, half of them were re-hired in off-farm work by April 2009. By August 2009, less than 2% of the rural labor force was unemployed due to the crisis. The robust recovery appears to have helped avoid instability.